Altering the Regiospecificity of a Catechol O‐methyltransferase through Rational Design: Vanilloid vs. Isovanilloid Motifs in the B‐ring of Flavonoids. Issue 21 (10th October 2022) - Dippe, Martin; Davari, Mehdi D.; Weigel, Benjamin; Heinke, Ramona; Vogt, Thomas; Wessjohann, Ludger A.
Abstract: Rational re‐design of the substrate pocket of phenylpropanoid‐flavonoid O ‐methyltransferase (PFOMT) from Mesembryanthemum crystallinum, an enzyme that selectively methylates the 3′‐position (= meta ‐position) in catechol‐moieties of flavonoids to guiacol‐moieties, provided the basis for the generation of variants with opposite, i. e. 4′‐ ( para ‐) regioselectivity and enhanced catalytic efficiency. A double variant (Y51R/N202W) identified through a newly developed colorimetric assay efficiently modified the para ‐position in flavanone and flavanonol substrates, providing access to the sweetener molecule hesperetin and other rare plant flavonoids having an isovanilloid motif. Abstract : Rational design : A plant O‐methyltransferase was engineered for higher activity and for opposite regioselectivity. Its variants are optimal tools for the production of bioactive flavonoids with a defined methylation pattern, e. g. for producing the natural sweetener hesperitin.